Effect of ramucirumab and bevacizumab in an experimental diabetic retinopathy rat model: A pilot study - Gungor, Sara Koylu; Kobat, Sabiha Gungor; Balbaba, Mehmet; Yildirim, Hakan; Ilhan, Nevin; Eroksuz, Yesari (Wolters Kluwer Medknow Publications, 2026)
Purpose: To compare the biochemical and histopathological effects of ramucirumab and bevacizumab in a streptozotocin (STZ)-induced experimental diabetic retinopathy (DR) rat model. Methods: A total of 40 adult male Sprague-Dawley rats were divided into four groups: Control, STZ, STZ + bevacizumab (2.5 mg/kg, intraperitoneal, single dose), and STZ + ramucirumab (8 mg/kg, intraperitoneal, single dose). Oxidative stress and inflammatory markers, including superoxide dismutase (SOD), interleukin-1 beta (IL-1 beta), and transforming growth factor beta-1 (TGF-beta 1), as well as vascular endothelial growth factor-A (VEGF-A) levels, were measured using enzyme-linked immunosorbent assay. Histopathological evaluations were performed using hematoxylin-eosin, periodic acid-Schiff, and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) staining. Statistical analyses were conducted using ANOVA and nonparametric tests (P < 0.05). Results: : STZ administration significantly increased VEGF-A and IL-1 beta levels while decreasing SOD levels. Both bevacizumab and ramucirumab significantly reduced VEGF-A and IL-1 beta levels and restored SOD values toward control levels. Histopathological analyses revealed that neovascularization, endothelial proliferation, basement membrane thickening, and vascular hyalinization observed in the STZ group were markedly reduced in the treatment groups. No significant difference in efficacy was detected between the bevacizumab and ramucirumab groups. Conclusion: Ramucirumab provided biochemical and histopathological improvements comparable to bevacizumab in the experimental DR model. These findings suggest that ramucirumab may represent an alternative or complementary option to existing anti-VEGF therapies in ophthalmology. Furthermore, the results highlight the simultaneous role of angiogenesis, inflammation, and oxidative stress in the pathogenesis of DR. Larger, longer-term studies with different dosing protocols are warranted.
Keywords: Bevacizumab; diabetic retinopathy; inflammation; oxidative stress; ramucirumab; rat model; VEGF; Bevacizumab; diabetic retinopathy; inflammation; oxidative stress; ramucirumab; rat model; VEGF